2015
DOI: 10.4103/0300-1652.150688
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of heart disease risk factors among workers in a Nigerian University: A call for concern

Abstract: Introduction:Cardiovascular disease is the commonest cause of mortality worldwide. Many risk factors predate the development of cardiovascular diseases. Adequate knowledge of risk factors for cardiovascular diseases is the first step towards effective preventive strategies to combat the cardiovascular diseases burden in any population. This study aims to determine the knowledge of workers in a Nigerian University on risk factors for cardiovascular diseases.Materials and Methods:A cross-sectional survey of 206 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
41
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 16 publications
15
41
6
Order By: Relevance
“…This was in line with a study among university staff and students in Nigeria [19] and in Michigan [35], though it contrasts with the ‘blurred, double or loss of vision’ mostly identified among Australian urban dwellers [15]. That our study population was more aware of stroke compared to heart attack, could be consistent with the fear of handicap among the general population and also with the growing incidence of stroke in our setting [36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was in line with a study among university staff and students in Nigeria [19] and in Michigan [35], though it contrasts with the ‘blurred, double or loss of vision’ mostly identified among Australian urban dwellers [15]. That our study population was more aware of stroke compared to heart attack, could be consistent with the fear of handicap among the general population and also with the growing incidence of stroke in our setting [36].…”
Section: Discussionsupporting
confidence: 91%
“…The overall low level of knowledge on CVD observed in our study is similar to findings among primary care physicians in the West region of Cameroon [17] and among university staff in Nigeria [19]. Similar worrisome knowledge levels have been obtained across other settings [10, 12].…”
Section: Discussionsupporting
confidence: 84%
“…However, most of them classified knowledge and awareness of CVD or the risk factors as poor, acceptable or good. In the study by Akintunde et al,[ 23 ] among university staff, a knowledge score of <50% was classified as low; 50–69% moderate and ≥70% good. Nakibuuka et al[ 24 ], in a study in Uganda classified urban and rural residents who could identify 5–10, 2–4 and <2 CVD risk factors or warning signs as having good, fair and poor knowledge respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, the studies reported generally low knowledge levels of CVDs with most studies reporting less than 50.0% of respondents having good knowledge. In studies conducted among workers in a Nigerian University Hospital, one reported that 19.0% had good knowledge of CVDs[ 23 ] while another showed that 53.5% knew the mechanism through which stroke occurs. [ 28 ] Findings on the knowledge and awareness of CVDs in SSA is summarized in Table 2 and Fig 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The world health organization (WHO) promotes knowledge of behavioral CVD risk factors [11]. Already, some studies have assessed knowledge of CVD and risk factors in Africa among the general community [12][13][14][15][16][17], while a few others have done so in speci c population groups [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%